Kinematic and dynamic analysis of running under conditions of variable gravity - Crupi, V.; La Rosa, G. (Bio-Medical Materials and Engineering, 1999)
A new training system was designed and realised by the engineer G. Scuderi: a centrifugal track for runners. The principal advantage of this track is to increase the forces on athlete during the run with an effect very similar to that of an "artificial gravity", so the athlete can develop more muscle power. A multibody numerical model of a runner was developed to analyse the behaviour of the athlete on the centrifugal track. The multibody model was calibrated by experimental analysis; in fact, the joint angles were measured by a digital image processing system and introduced as input in the numerical simulation. The numerical results obtained are the values of many kinematic and dynamic variables, in particular the ground reaction force and the moments in the hip, knee, and ankle joints. A comparison between the normal running and that on the centrifugal track was carried out, demonstrating the validity of training on the latter. The results of the numerical simulation confirm that the power developed during running on the track, and the corresponding work performed by the joints, is considerably greater than that found during normal running.